â€œArsitektur Panggungâ€ Di Kawasan Tugu Nasional - Yuke Ardhiati (LP2M ISBI Bandung, 2014)
ABSTRACTÂ The many of architecture works of Soekarno in the 1960s are express the Nation Pride by exploring the Indonesian culture as the basic design into Modern Architectureâ€™s buildings. This paper is a narra- tive of the spatial experiences in Soekarnoâ€™s masterpiece work, Tugu National. The study is refers to a qualitative research and used a Grounded Theory of Glaser and Strauss. By using a phenomenological spatial investigation in Tugu National building area was found an architecture drama analogy by adop- ted the sequences programming space looks like a drama performing especially from above through an aerial view of the Tugu National. The monument building looks like a resembled of â€˜the drama perform- ingâ€™ shown from a balcony on the aircraft cabin. A new theory named â€œArchitecture of Stageâ€ include to reveal Khora, as the concept of the â€˜architectural formâ€™ by traced the Soekarnoâ€™s ideas to express the uniqueness form of the monument. He composed an â€˜Architecture Dramaâ€™ analogy as his tacit know- ledge in â€˜tonil dramaâ€™ during his exile at Ende and Bengkulu. He reflected the Old Javanesse culture as the basic of the Modern Architecture design as an Architectureâ€™s Event at that time.Â Keywords: Architectureâ€™s Drama, Phenomenology, tonil drama of Soekarno, spatial investigation, Tugu National MonumentÂ Â Â Â ABSTRAKÂ Beberapa karya arsitektur Soekarno seputar tahun 1960-an merupakan ekspresi Nation Pride melalui eksplorasi budaya Indonesia sebagai basis perancangan bangunan Arsitektur Modern. Tulisan merupakan narasi pengalaman spasial pada karya masterpiece Soekarno, di kawasan Tugu Nasional berdasar penelitian kualitatif yang menerapkan strategi Grounded Theory meru- juk Glaser dan Strauss. Melalui pengamatan keruangan secara fenomenologi di kawasan Tugu Nasional telah ditemukan arsitektur drama analogy melalui cara mengadopsi sekuen ruang yang menyerupai pertunjukan drama, terutama melalui pandangan udara di kabin pesawat yang mengudara di atas kawasan Tugu Nasional, bagaikan Â pertunjukan drama yang disak- sikan dari sebuah balkon. Teori baru yang dinamai â€œArsitektur Panggungâ€ disertai Â pengung- kapan khora, sebagai konsep bentuk/â€™formâ€™ arsitektur Tugu Nasional yang ditelusur sebagai ide Soekarno. Ia telah menggubah arsitektur drama sebagai pengetahuan tacit semasa menggelar drama tonil di pembuangan Ende dan Bengkulu. Soekarno mengekspresikan budaya Jawa Kuno sebagai basis perancangan Arsitektur Modern, yang kini dinamai â€˜Arsitektur-Peristiwaâ€™.Â Kata kunci: â€œArsitektur Panggungâ€, fenomenologi, drama tonil, pengalaman keruangan, Tugu Nasional